Developing Instrument for Measuring the Implementation of Inclusive Education in Universities - Iswari, Mega; Armaini, Armaini; Zulmiyetri, Zulmiyetri; Nurhastuti, Nurhastuti; Safaruddin, Safaruddin (Angstrom Centre of Education, 2023)
This research aims to develop an instrument to measure the implementation of inclusive education in universities. The research was developed using mixed-methods approach which combines Theoretical Framework and Needs Assessment. The first stage of the research involved literature review to investigate the relevant instrument and references that support the development of instrument for measuring inclusive education in universities. The second stage was needs assessment conducted at universities in Padang. The subjects of the research were 47 university students from four universities in Padang. The data were analyzed using focus group discussion. The study of index for inclusion for higher education was compared to the results of the research. Findings of the research showed that there are five aspects needed to develop the instrument of index for inclusion in universities.